2015
DOI: 10.1371/journal.pone.0125826
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Immunological Failure among HIV Patients on HAART in Southern Ethiopia

Abstract: Immunological monitoring is part of the standard of care for patients on antiretroviral treatment. Yet, little is known about the routine implementation of immunological laboratory monitoring and utilization in clinical care in Ethiopia. This study assessed the pattern of immunological monitoring, immunological response, level of immunological treatment failure and factors related to it among patients on antiretroviral therapy in selected hospitals in southern Ethiopia. A retrospective longitudinal analytic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
37
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 31 publications
15
37
5
3
Order By: Relevance
“…This result is similar to the study reported from Southern Ethiopia. 14 This might be due to the higher rate of morbidity associated with the inability to identify failures early and switch to second-line regimen. This research identifies that patients with baseline CD4 count of <100 cells/mm 3 have higher odds of first-line ART failure, which is in line with studies conducted in Ethiopia at Debre Markos Hospital, 9 Addis Ababa public hospitals, 15 Bale Zone hospitals 11 and Gondar Teaching University Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the study reported from Southern Ethiopia. 14 This might be due to the higher rate of morbidity associated with the inability to identify failures early and switch to second-line regimen. This research identifies that patients with baseline CD4 count of <100 cells/mm 3 have higher odds of first-line ART failure, which is in line with studies conducted in Ethiopia at Debre Markos Hospital, 9 Addis Ababa public hospitals, 15 Bale Zone hospitals 11 and Gondar Teaching University Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…As a non-concurrent retrospective cohort, the study required data on exposure status at a specific earlier time-point (i.e., potential risk factors at the time of treatment onset), but also the identification of outcome events (i.e., death or censored) during the study period. Information on two important potential risk factors was not available in the healthcare records of HIV patients, i.e., JUSH: body mass index (BMI) [8,36,37,38] and viral load [39,40]. While the BMI could not be calculated due to the lack of the registered heights of patients in clinical records, measurements of viral loads were not available at the hospital during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] In Ethiopia, the prevalence of first-line ART failure ranges from 2.4% to 17.6%. [12][13][14][15] A rampant first-line ART failure imposed a major challenge to HIV prevention and control programs. The alternate treatments after first-line ART failure are limited due to the high cost and limited options of alternative medications.…”
Section: Introductionmentioning
confidence: 99%